Combined Expressive Writing and Progressive Muscle Relaxation to Reducing Anxiety and Stress Among Adolescent: a Case Study - Muhammad Muslih; Azzah Jihan Fa'izah (Dewan Pimpinan Daerah Persatuan Perawat Nasional Indonesia Kota Blitar, 2026)
Background: Adolescent mental health issues have become a global concern due to their impact on emotional regulation, academic achievement, and social functioning. Therefore, non-pharmacological interventions are a potential solution to address these issues. Objective: This study evaluated the effects of muscle therapy in reducing symptoms of anxiety and stress in adolescents. Methods: This single-case study was conducted over a one-month period. One female was purposively selected based on her Depression Anxiety Stress Scale-21 (DASS-21) results, which indicated very severe anxiety and moderate stress. The intervention consisted of eight sessions combining progressive muscle relaxation and expressive writing activities conducted in the participant's home. Data were collected through observation, therapeutic evaluation, and pre-post DASS-21 assessments. Results: The intervention resulted in substantial improvements in the participants' psychological well-being. Anxiety scores decreased from 22 (very severe) to 10 (moderate), while stress scores decreased from 20 (moderate) to 10 (normal). Depression scores remained within the normal range before and after the intervention. Participants also reported feeling emotional relief and more comfortable expressing their feelings during the therapy process. Conclusion: This intervention can be implemented as an alternative holistic strategy in public health and mental health nursing practice.